The Autonomy-Focused Approach in Higher Education: Theoretical Grounds and Practical Implications - Oksana A. Gavrilyuk (National Research Mordova State University, 2017)
Introduction: based on the analysis of both the current practice and theory of autonomy in education, this paper is intended to determine the core principles, conditions and practical opportunities for implementation of the autonomy-focused approach in Russian universities. Materials and Methods: to substantiate the benefits and reveal the core characteristics of the autonomy-focused approach in higher education, we performed the content-analysis of both national and international higher educational documents. The practical aspects of the autonomy-focused approach have been examined through applying the ideas of autonomy-focused education to the introduction of the G-MedEx international networking educational programme (the G-Med Ex Programme) at Professor V. F. Voino-Yasenetsky Krasnoyarsk State Medical University in 2015-2016. Analysis of the educational process outcomes and open discussions with teachers and students-participants of the G-MedEx Programme have also become an important source of information. Results: it was revealed that the development of the university educational environment actors' autonomy is possible though the use of the autonomy-focused approach, which represents a critical tool for implementation of the personality-centred educational paradigm. Among the core characteristics of the autonomy-focused approach in higher education we suggested the principles of innovative self-change, personal involvement and self-fulfillment, critical awareness and self-reflection, readiness to face challenges, interdisciplinary character of training, and practical focus of education. Investigating the practical aspects of the autonomy-focused approach, we demonstrated its benefits using the example of an international networking educational programme. Discussion and Conclusions: the results of the implementation of the autonomy-focused approach within the G-MedEx Programme suggest that using this approach is beneficial for both medical university students' and teachers' autonomy development. Practical relevance of the study is ensured through specifying the core principles, conditions and opportunities for implementation of the autonomy-focused approach in higher education, therefore allowing for possible application of the described approach in various universities and providing a basis for investigating its potential in other educ ational contexts.